A Comparison between Use of Spray and Freeze Drying Techniques for Preparation of Solid Self-Microemulsifying Formulation of Valsartan and In Vitro and In Vivo Evaluation. (18th July 2013) - Singh, Sanjay Kumar; Vuddanda, Parameswara Rao; Singh, Sanjay; Srivastava, Anand Kumar
Abstract : The objective of the present study was to develop self micro emulsifying formulation (SMEF) of valsartan to improve its oral bioavailability. The formulations were screened on the basis of solubility, stability, emulsification efficiency, particle size and zeta potential. The optimized liquid SMEF contains valsartan (20% w/w), Capmul MCM C8 (16% w/w), Tween 80 (42.66% w/w) and PEG 400 (21.33% w/w) as drug, oil, surfactant and co-surfactant, respectively. Further, Liquid SMEF was adsorbed on Aerosol 200 by spray and freeze drying methods in the ratio of 2 : 1 and transformed into free flowing powder. Both the optimized liquid and solid SMEF had the particle size <200 nm with rapid reconstitution properties. Both drying methods are equally capable for producing stable solid SMEF and immediate release of drug in in vitro and in vivo conditions. However, the solid SMEF produced by spray drying method showed high flowability and compressibility. The solid state characterization employing the FTIR, DSC and XRD studies indicated insignificant interaction of drug with lipid and adsorbed excipient. The relative bioavailability of solid SMEF was approximately 1.5 to 3.0 folds higher than marketed formulation and pure drug. Thus, the developed solid SMEF illustrates an alternative delivery of valsartan as compared to existing formulations with improved bioavailability.